The Influence of Interpersonal Communication, Innovative Behaviour and Self-Determination on Teacher Performance - Netty Zakiah; Candra Wijaya; Wahyudin Nur Nasution (Journal Evaluation in Education (JEE), 2025)
Purpose of the Study: This study aims to analyze the effects of interpersonal communication, innovative behavior, and self-determination on teachers' performance at Madrasah Aliyah Negeri in Medan City. Methodology: The research was conducted at Madrasah Aliyah Negeri in Medan, with teachers as participants. A quantitative research design was applied using a simple random sampling technique based on the Slovin formula. Main Findings: The findings indicate that interpersonal communication, innovative behavior, and self-determination directly and indirectly impact teacher performance. These factors significantly enhance the teaching quality in Madrasah Aliyah Negeri in Medan City. The study underscores the importance of fostering effective interpersonal communication, encouraging innovative behavior, and promoting self-determination to improve teacher performance. Although the study identifies key factors influencing performance, it also acknowledges that other variables might contribute to teacher effectiveness, which were not explored in this research. Novelty/Originality of the Study: This research offers insights into how interpersonal communication, innovative behavior, and self-determination shape teacher performance, specifically within Madrasah Aliyah Negeri in Medan. These factors have not been extensively studied in this setting, making this research an essential addition to the field. The study highlights the importance of developing strategies that improve communication, foster innovation, and enhance teacher autonomy to boost teacher performance and educational outcomes.